2020
DOI: 10.1016/j.celrep.2020.107895
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Recycling by ABCE1 Links Lysosomal Function and Iron Homeostasis to 3ʹ UTR-Directed Regulation and Nonsense-Mediated Decay

Abstract: Highlights d A genome-wide CRISPR screen identifies regulators and components of the NMD pathway d ABCE1 is required for NMD and other forms of 3ʹ UTRmediated regulation d Upon ABCE1 loss, ribosomes move into 3ʹ UTRs and displace bound regulators d Iron deficiency and oxidative stress impair ABCE1 and posttranscriptional control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 102 publications
(158 reference statements)
8
41
0
Order By: Relevance
“…After 60S dissociation, a complex including eIF2D/Tma64 (the homolog of eIF2D in yeast), MCST1/Tma20, and DENR/Tma22 is required for 40S ribosome recycling in yeast, and mutation of this complex leads to reinitiation at 3´UTRs [131][132][133] . In general, translation termination is a highly controlled process, with the binding of 80S ribosomes to 3´UTRs only being demonstrated in either terminally differentiated erythrocytes or in the context of mutated translational machinery [79][80][81][82][83][84]134 . In our study, the regulation of ribosome recycling occurs during meiosis prophase in cells that are not terminally differentiated, as spermatocytes will undergo two more rounds of cell division, weeks of further differentiation, and continued protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…After 60S dissociation, a complex including eIF2D/Tma64 (the homolog of eIF2D in yeast), MCST1/Tma20, and DENR/Tma22 is required for 40S ribosome recycling in yeast, and mutation of this complex leads to reinitiation at 3´UTRs [131][132][133] . In general, translation termination is a highly controlled process, with the binding of 80S ribosomes to 3´UTRs only being demonstrated in either terminally differentiated erythrocytes or in the context of mutated translational machinery [79][80][81][82][83][84]134 . In our study, the regulation of ribosome recycling occurs during meiosis prophase in cells that are not terminally differentiated, as spermatocytes will undergo two more rounds of cell division, weeks of further differentiation, and continued protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…RNA decay may also be promoted by the CCR4‒NOT deadenylase complex recruited by the SMG5‒SMG7 dimer. Additional NMD factors have recently been identified from NMD reporter-based genome-wide loss-of-function screens ( Alexandrov et al, 2017 ; Zhu et al, 2020 ), although their exact functions in NMD are not fully understood.…”
Section: Mechanisms Of Translation-dependent Mrna Surveillancementioning
confidence: 99%
“…Yeast ribosome profiling assays also demonstrated the role that Dom34 plays in recycling ribosomes that escape stop codon and enter downstream non-coding regions [ 135 , 136 ]. In this sense, defects in ISC delivery to ABCE1 due to oxidative stress or lysosomal dysfunction cause stop codon readthrough and ribosome movement into 3′UTRs [ 137 ]. Thus, both ABCE1/Rli1 and Dom34/Pelota are necessary for the access of post-transcriptional regulatory RNA-binding proteins to the 3′UTR of mRNAs since the movement of a single ribosome through the 3′UTR in ABCE1-defective cells is sufficient to displace mRNA-bound proteins [ 137 ].…”
Section: Iron Is Required For Translation Terminationmentioning
confidence: 99%
“…In this sense, defects in ISC delivery to ABCE1 due to oxidative stress or lysosomal dysfunction cause stop codon readthrough and ribosome movement into 3′UTRs [ 137 ]. Thus, both ABCE1/Rli1 and Dom34/Pelota are necessary for the access of post-transcriptional regulatory RNA-binding proteins to the 3′UTR of mRNAs since the movement of a single ribosome through the 3′UTR in ABCE1-defective cells is sufficient to displace mRNA-bound proteins [ 137 ]. Recent data have demonstrated that non-sense mediated decay and post-transcriptional regulatory pathways such as microRNA and ARE-mediated decay are impaired upon depletion of ABCE1 [ 137 ].…”
Section: Iron Is Required For Translation Terminationmentioning
confidence: 99%